FACTORS CAUSES ORAL COMMUNICATION APPREHENSION OF ENGLISH DEPARTMENT STUDENTS IN PRESENTATION CLASS AT RIAU ISLAMIC UNIVERSITY - Vitri Angraini Hardi (Universitas Pahlawan Tuanku Tambusai, 2017)
Ability to communicate orally in Foreign Language still meets some obstacles for language learners in Indonesia. It seems a hard task to do. The learning experiences on English subject are still not sufficient for the language learners to enable them to communicate in English orally. Some previous studies showed that the students external factors are the obstacle cause their inability to communicate in Foreign Language such as the lack of the vocabulary, law of motivation, the lack amount of practice and the monotonous teaching strategy. However, since the communication process is not only involving the physical aspect, the psychological aspects should be recognized as the potential factor that might hinder students ability to communicate orally in Foreign Language. The present study showed that the students psychological factors, namely apprehension plays the role hinder the students ability to communicate. The findings showed that there were four factors cause the students inability to communicate in English as foreign language, namely 1) the ability on language, 2) the lecturers evaluation, 3) the communication task type, and 4) lecturers feedback.